Engaged or Not? A Comparative Study on Factors Inducing Work Engagement in Call Center and Service Sector Work - Mustosmäki, Armi; Anttila, Timo; Oinas, Tomi (Nordic Journal of Working Life Studies, 2013)
The aim of this study was to compare the possibilities of experiencing positive well-being in call centers and other service sector work. The article focuses on the prevalence of working conditions (job demands, autonomy, and social support) in call centers and at other service sector workplaces and how these factors are related to work engagement. In addition, we examine whether the relationships are divergent in call centers in comparison to other service sector work. Analysis is based on the data provided by the “Quality of Life in Changing Europe” project. The survey data were collected from service sector organizations (retail, banking, and insurance) and a telecom organization’s call center functions in Finland (N = 967). According to our results, work engagement in call center environment is challenging due to the strong negative effect of job demands. In general, call center employees experienced less feelings of engagement than employees in the comparison organizations. This difference remained significant even after controlling for background factors and measures of working conditions. In addition, we found significant differences between call center and other service sector organizations in the effects of both autonomy and demands. The levels of autonomy and work demands proved to be strong antecedents of perceived work engagement, especially in call center environment.